GAMBARAN FAKTOR RISIKO PENYAKIT HIPERTENSI PADA WARGA BINAAN PEMASYARAKATAN (STUDI DI LAPAS KLAS IIA WANITA KOTA SEMARANG) - Moch Ardyan Pratama Putra; Henry Setyawan Susanto; Lintang Dian Saraswati; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Hypertension is a health problem that occurs in Prison Class IIA Women Semarang with the prevalence in 2015 of about 28.6%. The purpose is to identify risk factors of hypertension on inmates. The design study is observational a cross sectional study approach at 100 inmates and statistical test with Chi-Square. The result obtained is an increased proportion of hypertension (43%), patients with hypertension more at age ≥40 years (53.8%); have a family history of disease associated with hypertension; have a history of smoking (52.9%); have a history of alcohol consumption (52.4%); the status of obesity (51.4%); as illicit drug users (51.7%); experiencing stress (48.1%); has long incarceration >1 year (44.8%); lack of family support (45.2%); lack of physical activity (45.1%); and used to consume salty (57.7%). Inmates need to replace smoking with eating fruits and vegetables to avoid overweight/obesity, and following rehabilitation in prisons in order to reduce the effects of illicit drugs and reduce the risk of hypertension.